Transition to the revised OHADA law on accounting and financial reporting: Corporate perceptions of costs and benefits - Micheal Forzeh Fossung; Lious Agbor Tabot Ntoung; Helena Maria Santos de Oliveira; Cláudia Maria Ferreira Pereira; Susana Adelina Moreira Carvalho Bastos; Liliana Marques Pimentel (Journal of Risk and Financial Management, 2020)
This paper examines the ongoing transition to the revised Organisation for the Harmonisation of Business Law in Africa Act on Accounting and Financial Reporting for companies in general and to the International Financial Reporting Standards for listed and group companies with a particular focus on recent institutional developments and corporate concerns. The study used 80 professional accountants, most of whom were members of the Institute of Chartered Accountants of Cameroon and academics. Using the descriptive statistics, the study shows that the transition to the revised OHADA brings about a high level of comparability and transparency of the financial statements, that the International Financial Reporting Standards can be implemented in Cameroon (but not fully), and that the benefit of the transition exceeds the cost.
Keywords: 330; comparability; IFRS; OHADA accounting; perception; transition